2017
DOI: 10.1177/0885066617726753
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis at a Safety Net Hospital: Risk Factors Associated With 30-Day Readmission

Abstract: At a safety net hospital, patients who survived their initial sepsis hospitalization had a 30-day readmission rate to our institution of 22.6% that is comparable to rates described in prior studies. Readmission was commonly due to infection. Factors associated with readmission included multiple comorbid medical conditions, bacteremia, and being discharged with a vascular catheter. Further studies in this population are needed to determine potential modifiability of these risk factors in an attempt to reduce se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Ten studies report a sepsis cohort starting from their index admission [27,35,37,41,44,46,50,51,53,55], twelve studies report a sepsis survivor cohort [9, 12, 30-32, 36, 45, 47, 52, 56, 58, 59], and four report a rehospitalisation cohort [28,34,40,42]. Ten were single-centre studies [28,37,40,44,47,50,51,55,56,59] with greater risk of bias compared to 21 studies [9, 12, 13, 27, 29-31, 33, 35, 36, 38, 39, 41, 42, 45, 48, 49, 53, 54, 57] that used large multi-centre databases with greater generalizability. Five studies that use notes review for outcome assessment [28,37,40,51,55] have a greater risk of ascertainment bias, compared to studies that use record linkage outcome assessment.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…Ten studies report a sepsis cohort starting from their index admission [27,35,37,41,44,46,50,51,53,55], twelve studies report a sepsis survivor cohort [9, 12, 30-32, 36, 45, 47, 52, 56, 58, 59], and four report a rehospitalisation cohort [28,34,40,42]. Ten were single-centre studies [28,37,40,44,47,50,51,55,56,59] with greater risk of bias compared to 21 studies [9, 12, 13, 27, 29-31, 33, 35, 36, 38, 39, 41, 42, 45, 48, 49, 53, 54, 57] that used large multi-centre databases with greater generalizability. Five studies that use notes review for outcome assessment [28,37,40,51,55] have a greater risk of ascertainment bias, compared to studies that use record linkage outcome assessment.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…Readmission after a hospital stay is a significant contributor to healthcare costs and may be preventable. Early readmission, within the first few days after the initial discharge, has been reported to be unusually high for some conditions and places a substantial economic burden on the healthcare system (7)(8)(9). The rate of readmission for cirrhosis is high and is associated with a significant economic impact.…”
Section: Introductionmentioning
confidence: 99%
“…The odds of readmission in individuals with CKD are unduly high, with a strong body of literature indicating that CKD is associated with up to twice the odds of all‐cause readmission compared to the general population (Ayatollahi et al, 2018; Weinreich et al, 2017). A retrospective cohort study revealed that patients with kidney failure have a 379% higher odds of being readmitted to the hospital within 30 days than pre‐kidney failure (Jasinski et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%